(untitled) (Eurasian Scientific Herald, 2023)
The actual significance of this topic of the article lies in the fact that information competence increasingly determines the level of distance education. The statement about the beginning of the transition of human civilization to a new qualitative state is indisputable (“post-industrial” or “information” culture is replacing the “industrial” one). Each stage of the development of society has its own form and content of the process of teaching new generations, transferring accumulated knowledge, skills, and traditions to them. The purpose of this work is to develop new, more interesting, more effective, from the point of view of pedagogy and psychology, interactive methods, so that they include different psychophysiological characteristics of students and give the maximum result in the educational process of a distance learning.